PERAN KOMITE SEKOLAH DALAM PENGAWASAN PROGRAM BANTUAN OPERASIONAL SEKOLAH DI SMP NEGERI 05 RUPAT KABUPATEN BENGKALIS - Amri, Fahmi; Sahuri, Chalid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The eKeywords: Role Of The School Committee. Supervision. The BOS Program. RKASstablishment of school Committee based on the decision of the Minister of national education Number O44/U/2002 as a standalone institution/agency story based on each unit of education aims to confront and channeling apirasi/community initiatives in the operational policy of the school to give birth as well as encouraging the role of the community. creating a transparent atmosphere. accountable, democratic and in organizing and educational services in the education unit. As part of organizing education, supervision and the school Committee role in the BOS program in educational units begins as the giver consideration and support for the preparation of the plan of activities of the school budget (RKAS) Fund BOS. Later, the school Committee also plays an active role in monitoring the BOS Programme implementation.In this study, the theory concept is the theory advanced by supervision Brantas, explained that the oversight in an activity/program includes process sets the standard (the role). the Act assessment and conduct the stair steps of improvement. If there are deviations in order for the purpose of implementation and according to plan. The research method used is descriptive qualitative method of data collection instruments include observation, interviews. the study of library-related research objectives.The research results show that the Committee role of State junior school 5 Rupat in oversight of Operational Assistance Program School (BOS) in the state Junior high school 5 Rupat of Bengkalis Regency has not run optimally. where the school Committee does not play a role in giving considerations compose RKAS and embody and encourage community participation in program activities of the BOS. The school Committee also did not perform the Act assessment on the implementation of the BOS programme with a plan that has been set. Consequently there is no corrective actions (correction) done School Committee.Keywords: Role Of The School Committee. Supervision. The BOS Program. RKAS